Jelica Belović Bernadžikovska on the “National Spirit” (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The ethnographic work of Jelica Belović Bernadzikowska, aimed at the development and classification of ornaments and embroidery techniques, was marked by the strong positioning of folk textile art in the context of South Slavic folklore. This scientific approach is characterized by ideas on the individuality of South Slavic embroidery, specific national spirit that permeates this kind of creative art and distinct intertwining of different types of art, especially poetry and textile ornamentation. By observing national embroidery in the context of larger folklore heritage, the author points to the significance of the creative process as a compound of tradition and individual talent, as well as its complex nature. The notion of national embroidery as the materialization of the national thoughts, feelings and traditions has contributed to the fact that the study of Jelica Belović Bernadzikowska represents a veritable treasure trove of short forms of folklore, passages, beliefs and other echoes of national spirit.
Keywords: Jelica Belović Bernadzikowska; embroidery; embroiderer; textile; national tradition